Intestinal microflora of white mice and guinea pigs in experimental antibiotic-associated dysbacteriosis and the possibility of its correction whith prebiotic stimbifid - I. Yu. Chicherin; I. V. Darmov; I. P. Pogorelsky; I. A. Lundovskikh (Журнал инфектологии, 2014)
Analysis of the composition of intestinal microflora of white mice and guinea pigs in an experimental antibiotic-associated dysbacteriosis and assessment of the possibility of its correction with prebiotic Stimbifid. White mice and guinea pigs in an experimental antibiotic-associated dysbacteriosis were used in the experiments. The recovery of their own intestinal microflora of laboratory animals was evaluated after prebiotic Stimbifid oral administration. The positive effect of prebiotic Stimbifid has been found to restore their own intestinal microflora of white mice and guinea pigs, including Bifidobacteria, Lactobacillus and Escherichia. Prebiotic Stimbifid has been shown to be useful for the correction of the intestinal microflora of laboratory animals in an experimental antibiotic-associated dysbacteriosis.